Evolutionary–based channel assignment in multi–radio multi–channel wireless mesh networks for multicast applications. (22nd May 2013) - Vaezpour, Elaheh; Dehghan, Mehdi
The multi–radio multi–channel wireless mesh networks give rise to considerable improvement in network throughput. Due to the limited number of available orthogonal channels, interference is still a problematic issue in such networks. Besides, multicast is an effective mechanism for delivering data to a group of receivers. Channel assignment for multicast has only been addressed recently. Focusing on this issue, in this paper, we consider the multicast channel assignment problem to minimise the interference among multicast tree nodes. We develop a hybrid particle swarm optimisation (PSO) and tabu search approach for channel assignment. The use of tabu search as a local improvement procedure enables the proposed algorithm to overleap local optimum and show satisfactory performance. The proposed approach is applied to different network configurations, and its performance is compared with LCA, MCM, tabu search–based, and PSO–based algorithms. Simulation results show that the proposed method achieves superior performance in terms of interference.